The Food Identity of Countries Differs Between Younger and Older Generations: A Cross-Sectional Study in American, European and Asian Countries - Frez-Muñoz, Lucía; Kampen, Jarl K.; Fogliano, Vincenzo; Steenbekkers, Bea L. P. A. (Frontiers in Nutrition, 2021)
Current generations have been strongly influenced by mass communication and massive immigration flows, which may change local lifestyles and perceptions of inhabitants towards traditional foods and beverages (TFB). TFB constitute a core element of countries’ cultural identity, although some of them are losing their appeal. Here, we studied the TFB-perceptions of inhabitants in nine countries to determine if their food identity is changing by analysing the TFB most frequently mentioned by different age cohorts within a country. Six countries were found to have a distinctive core of TFB shared across age cohorts (homogenous), while the remaining showed a heterogeneous pattern. Correspondence and cluster analyses usually grouped younger generations together implying higher similarities among these cohorts, Furthermore, the binary logistic regression analyses performed identified significant differences in the probability of mentioning a specific TFB across age cohorts per country. Data collected show younger cohorts focusing on TFB categorised as snacks and foods on-the-go, while older cohorts more often refer to time-consuming savoury preparations. The results suggest that lifestyles and current societal trends in food consumption, e.g. convenience and healthiness, are impacting on the food culture and identity of countries, and therefore play an important role in the variation of TFB perception and consumption between age cohorts within countries. The results obtained in this study could be used by food policy makers and nutritionists to distinguish the current trends that are reshaping the food identity and eating behaviours of the population, but also to improve or develop new dietary strategies by age cohorts in the countries studied.